2015
DOI: 10.1016/j.mce.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal soma-derived factor (gsdf), a TGF-beta superfamily gene, induces testis differentiation in the teleost fish Oreochromis niloticus

Abstract: Highlights・ Gsdf is expressed predominantly in XY gonads in the Nile tilapia.・ Gsdf expression pattern shows sexual dimorphism before morphological differentiation.・ Gsdf expression is the earliest gene expression detected in testis differentiation.・ Overexpression of gsdf is sufficient to induce testis differentiation in XX tilapia.Abbreviations: transforming growth factor-beta (TGF-beta), gonadal soma-derived factor (gsdf), doublesex/mab-3-related transcription factor-1 (Dmrt1), days post-hatching (dph), qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 66 publications
4
46
0
Order By: Relevance
“…In phylogenies, GDF9 and BMP15 generally group as sister clades variably related to gsdf (Sawatari et al, ; Shibata et al, ; Gautier et al, ; Myosho et al, ; Forconi et al, ; Horiguchi et al, ; Kaneko et al, ). Our comparative genomic investigations found that GDF9 , BMP15 , and gsdf ; are all near Aff family genes, which occupy paralogous chromosome segments in the human genome (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In phylogenies, GDF9 and BMP15 generally group as sister clades variably related to gsdf (Sawatari et al, ; Shibata et al, ; Gautier et al, ; Myosho et al, ; Forconi et al, ; Horiguchi et al, ; Kaneko et al, ). Our comparative genomic investigations found that GDF9 , BMP15 , and gsdf ; are all near Aff family genes, which occupy paralogous chromosome segments in the human genome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because phylogenetic analyses of TGFB family genes disagree on the affinities of gsdf (Sawatari et al, 2007;Shibata et al, 2010;Gautier et al, 2011a;Myosho et al, 2012;Forconi et al, 2013;Horiguchi et al, 2013;Kaneko et al, 2015), we analyzed conserved syntenies to learn which tetrapod TGFB genes are most closely related to those of fishes. Results showed that zebrafish gsdf shares conserved syntenies with gsdf of spotted gar (Fig.…”
Section: Origin Of Gsdfmentioning
confidence: 99%
“…Complete femaleto-male sex reversal of the medaka O. sakaizumii but not of O. latipes stimulated gsdf and subsequently dmrt1 [Horie et al, 2016]. In tilapia, upregulation of gsdf transcripts were initially suggested to be at 8 dpf prior to dmrt1 and localized also in the somatic cells surrounding germ cells [Kaneko et al, 2015]. However, CRISPR/Cas9 knockouts revealed that gsdf is in fact expressed after dmrt1 and an aromatase inhibitor treatment rescued the testicular phenotype of XY gsdf -/-gonads .…”
Section: New Actors Of Sex Determination and Differentiationmentioning
confidence: 96%
“…The best way to obtain monosex populations is through genetic control. Recently, researchers found that gsdf transgenic XX tilapia showed normal testis development (Kaneko et al ). In addition, our group found that the XX fish with amhy transgene displayed female‐to‐male sex reversal with functional testis (Li et al ).…”
Section: Modification Breedingmentioning
confidence: 99%